Applied physics, system science and computers II : proceedings of the 2nd International Conference on Applied Physics, System Science and Computers (APSAC2017), September 27-29, 2017, Dubrovnik, Croatia /: proceedings of the 2nd International Conference on Applied Physics, System Science and Computers (APSAC2017), September 27-29, 2017, Dubrovnik, Croatia. ([2019]) - Unknown
No abstract available